2021
DOI: 10.1101/2021.02.05.429875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex pheromone signal and stability covary with fitness

Abstract: If sexual signals are costly to produce or maintain, covariance between signal expression and fitness is expected. This signal-fitness covariance is important evolutionarily, because it can contribute to the maintenance of genetic variation in signal traits, despite selection from mate preferences. Chemical signals, such as moth sex pheromones, have traditionally been assumed to be stereotypical species-recognition signals, but their relationship with fitness is unclear. Here we test the hypothesis that for ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The data and scripts corresponding to this paper are archived online in the Dryad Digital Repository: [77].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…The data and scripts corresponding to this paper are archived online in the Dryad Digital Repository: [77].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…Previously, genetic mapping studies revealed several QTL underlying difference in sex pheromone composition in H. subflexa (Groot et al, 2013). Since variation in pheromone composition in H. subflexa is also explained by fitness variation (Blankers et al, 2021), many different genetic factors likely contribute small additional fractions to the total variance. Another explanation comes from population genetics: re-orientation of genetic covariances in response to bottlenecks may free up additive genetic variance, thereby paradoxically increasing levels of genetic variance (Carson, 1990;Templeton, 2008).…”
Section: No Change In Genetic Variancementioning
confidence: 99%
“…Specifically, the correlation between Z11-16:OH and Z11-16:OAc changed in both sign and magnitude. Since both Z11-16:OH and Z11-16:OAc reduce heterospecific mate attraction (Vetter and Baker, 1983;Vickers and Baker, 1997), and both traits covary with fitness and are condition-dependent (Blankers et al, 2021), the negative genetic correlation in the starting population could be the result of a trade-off that is selected against when artificial selection favors higher rates of acetates.…”
Section: Changing Genetic Covariancementioning
confidence: 99%
“…Pheromones can be costly to produce and maintain (Blankers et al, 2021;Harari et al, 2011) and variation occurs both within the individual lifespan and between individuals (De Pasqual et al, 2021;Blankers et al, 2021;Pham et al, 2021). Through pheromone variation and the use of signaling strategies, females can exert sexual selection on males by manipulating the arrival of males (Greenfield, 1981;Johnson et al, 2017a) and alter intrasexual dynamics by outcompeting same-sex conspecifics (Pham et al, 2020(Pham et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%